Biblioteca do Ministério da Mulher, da Família e dos Direitos Humanos - (:unkn) unknown (Instituto Brasileiro de Informação em Ciência e Tecnologia, 2020)
This book describes the evolution of the Library of the Ministério da Mulher, Família e Direitos Humanos (BMMFDH), which starts to act more actively in the ministry, within the scope of research project signed with Ibict. Studies have developed methods and standards to meet the informational needs with the use of new technologies, with the use of of free software for the management of information systems. Also noteworthy are the studies aimed at adapting the digital library to accessibility and studies on patrimonial rights, presenting innovations that can be replicated to other digital libraries of Government agencies. In this way, it is expected to contribute to the discussion on government libraries, that play a fundamental role in public administration and in preserving the agency's knowledge.
Keywords: Biblioteca de governo; Sistemas de informação; Biblioteca especializada; Ações sociais; Biblioteconomia